Pemberdayaan Masyarakat Desa Cupel melalui Produksi Jelly Coco Berbasis Kelapa Muda - Feerzet Achmad; Syahrizal Nasution; Rafael Denny Sihotang; Akhdan Ara Dzaky; Azahlea Sukesih; Muhammad Alif Anzami; Siti Maria Fentriyana Salma; Lestari Lestari; Muhammad Irsyad Abdullah; Kasih Pilia (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2026)
The partner’s main problem in this community service program was the suboptimal utilization of young coconuts in Cupel Village, Negara District, Jembrana Regency, despite their abundant availability and high economic potential. The priority problems faced by the PKK women’s group included limited knowledge of young coconut processing, production skills, the use of simple equipment, packaging techniques, and digital marketing. This community service program aimed to improve the capacity of coastal communities to process young coconuts into Jelly Coco, a value-added product with potential as an alternative source of income. The program was implemented using a participatory approach based on Participatory Rural Appraisal (PRA), which included needs identification through surveys and interviews, workshops, hands-on Jelly Coco production practice, Instagram-based marketing assistance, and evaluation through pre-test and post-test assessments. The activity involved 35 participants consisting of PKK members and representatives of the local community. The evaluation results showed an increase in the average achievement of participants’ knowledge and skills indicators from 72.65% in the pre-test to 95.57% in the post-test. Participants were also able to understand the functions of production equipment, the stages of Jelly Coco production, packaging techniques, and demonstrated strong interest in developing household-scale businesses based on young coconuts. Therefore, Jelly Coco production training effectively strengthened the technical and entrepreneurial capacity of the Cupel Village community. However, program sustainability still requires further support in marketing development, production equipment availability, and regular business mentoring.